Membangun Kepribadian Muslim dan Sumber Daya Manusia yang berkualitas melalui Revitalisasi Pendidikan Islam - Hana Zafira Zahra Subagyo; Maulidah Syahrisyarifah; M. Yunus Abu Bakar (JURNAL ILMIAH NUSANTARA, 2024)
education philosophy and its relevance to human resource (HR) development. Islamic education is viewed as a holistic effort encompassing the development of spiritual, intellectual, and moral dimensions. The process of shaping a Muslim personality begins with tazkiyah al-nafs (purification of the soul) to build character rooted in noble morals. Factors such as the family environment, formal education, and social culture contribute to personality formation. This article also highlights the role of Islamic education in creating human resources that are not only professionally competent but also possess strong moral integrity. In the era of globalization, Islamic education serves as a foundation to produce individuals capable of addressing contemporary challenges while adhering to Islamic values. The article emphasizes the importance of a value-based educational approach that integrates faith, knowledge, and practice as an effort to realize quality human resources within the context of both worldly and spiritual life